Distinct pathways for evolution of enhanced receptor binding and cell entry in SARS-like bat coronaviruses. - Alexandra L Tse; Cory M Acreman; Inna Ricardo-Lax; Jacob Berrigan; Gorka Lasso; Toheeb Balogun; Fiona L Kearns; Lorenzo Casalino; Georgia L McClain; Amartya Mudry Chandran; Charlotte Lemeunier; Rommie E Amaro; et al. (PLoS Pathogens)
Understanding the zoonotic risks posed by bat coronaviruses (CoVs) is critical for pandemic preparedness. Herein, we generated recombinant vesicular stomatitis viruses (rVSVs) bearing spikes from divergent bat CoVs to investigate their cell entry mechanisms. Unexpectedly, the successful recovery of rVSVs bearing the spike from SHC014-CoV, a SARS-like bat CoV, was associated with the acquisition of a novel substitution in the S2 fusion peptide-proximal region (FPPR). This substitution enhanced viral entry in both VSV and coronavirus contexts by increasing the availability of the spike receptor-binding domain to recognize its cellular receptor, ACE2. A second substitution in the S1 N-terminal domain, uncovered through the rescue and serial passage of a virus bearing the FPPR substitution, further enhanced spike:ACE2 interaction and viral entry. Our findings identify genetic pathways for adaptation by bat CoVs during spillover and host-to-host transmission, fitness trade-offs inherent to these pathways, and potential Achilles' heels that could be targeted with countermeasures.